M cell maturation and cDC activation determine the onset of adaptive immune priming in the neonatal Peyer's patch - Torow, Natalia; Li, Ronghui; Hitch, Thomas Charles Adrian; Mingels, Clemens; Al Bounny, Shahed; van Best, Niels; Stange, Eva Lena; Simons, Britta; Maié, Tiago; Rüttger, Lennart; Gubbi, Narasimha Murthy Keshava Prasad; Abbott, Darryl Adelaide; et al. (Immunity, 2023)
Early-life immune development is critical to long-term host health. However, the mechanisms that determine the pace of postnatal immune maturation are not fully resolved. Here, we analyzed mononuclear phagocytes (MNPs) in small intestinal Peyer's patches (PPs), the primary inductive site of intestinal immunity. Conventional type 1 and 2 dendritic cells (cDC1 and cDC2) and RORgt+ antigen-presenting cells (RORgt+ APC) exhibited significant age-dependent changes in subset composition, tissue distribution, and reduced cell maturation, subsequently resulting in a lack in CD4+ T cell priming during the postnatal period. Microbial cues contributed but could not fully explain the discrepancies in MNP maturation. Type I interferon (IFN) accelerated MNP maturation but IFN signaling did not represent the physiological stimulus. Instead, follicle-associated epithelium (FAE) M cell differentiation was required and sufficient to drive postweaning PP MNP maturation. Together, our results highlight the role of FAE M cell differentiation and MNP maturation in postnatal immune development.
CRIS-Team Scopus Importer:2023-06-23
Keywords: cDC2; dendritic cell; M cell; microbiota; neonatal immunology; Peyer's patch; post-natal establishment of intestinal homeostasis; RORgt